2013
DOI: 10.1073/pnas.1217712110
|View full text |Cite
|
Sign up to set email alerts
|

Transposon mutagenesis identifies genes essential for Plasmodium falciparum gametocytogenesis

Abstract: Gametocytes are essential for Plasmodium transmission, but little is known about the mechanisms that lead to their formation. Using piggyBac transposon-mediated insertional mutagenesis, we screened for parasites that no longer form mature gametocytes, which led to the isolation of 29 clones (insertional gametocyte-deficient mutants) that fail to form mature gametocytes. Additional analysis revealed 16 genes putatively responsible for the loss of gametocytogenesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
82
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(84 citation statements)
references
References 64 publications
(83 reference statements)
1
82
0
Order By: Relevance
“…It appears that a key step in Plasmodium gametocytogenesis is accomplished by transcriptional repression via an AP2 family transcription factor that blocks asexual replication and promotes conversion to the sexual stage (40). In fact, the P. falciparum ortholog of the principal AP2 gene identified in our study has been associated with transcriptional regulation of gametocytogenesis (41). Similarly, processes governing hypnozoite dormancy and activation that underlie P. vivax relapse may be under epigenetic regulation.…”
Section: Discussionmentioning
confidence: 80%
“…It appears that a key step in Plasmodium gametocytogenesis is accomplished by transcriptional repression via an AP2 family transcription factor that blocks asexual replication and promotes conversion to the sexual stage (40). In fact, the P. falciparum ortholog of the principal AP2 gene identified in our study has been associated with transcriptional regulation of gametocytogenesis (41). Similarly, processes governing hypnozoite dormancy and activation that underlie P. vivax relapse may be under epigenetic regulation.…”
Section: Discussionmentioning
confidence: 80%
“…The ortholog of this gene is resistant to genetic disruption in P. berghei (9), and its role in parasite development has not been investigated previously, although its putative function in gametocytogenesis was implicated in a previous study of P. falciparum parasites (24,25). Here, we successfully disrupted the Pyap2-g3 gene and showed that disruption of this gene significantly reduced the numbers of male and female gametocytes (Fig.…”
Section: Resultsmentioning
confidence: 89%
“…Our results also demonstrate that PY17X_1417400 (Pyap2-g3) is a gene that plays an important role in gametocyte development. Interestingly, the insertion of a transposon into the coding sequence of the P. falciparum ortholog gene (PF3D7_1317200) resulted in the absence of gametocytes, suggesting that it might play a role in gametocytogenesis; however, the role of the ortholog of this gene in gametocytogenesis could not be conclusively determined because the parasite line containing a transposon insertion in the PF3D7_1317200 gene also had a missense mutation in the Pfap2-g gene (24,25). Our data clearly showed that disruption of Pyap2-g3 significantly reduced the number of gametocytes, leading to the absence of sporozoites even though a small number of day 8 oocysts were observed (Fig.…”
Section: Figmentioning
confidence: 99%
“…One of the best examples of mutagenesis using piggyBac is in vivo mutagenesis in mice for cancer gene discovery. Traditionally, murine leukemia virus and murine mammary tumor virus were used (80,107,135) for oncogene discovery in hematopoietic cells (71,72) and mammary tissues (73), respectively. However, such experiments were not possible in a large fraction of solid tumors due to the limited accessibility of these retroviruses.…”
Section: Piggybac-mediated Genetic Screeningmentioning
confidence: 99%
“…By scaling up the experimental scale, one can generate a library of mutant parasites. A small library consisting of 189 parasites with piggyBac insertion was recently generated and, from this library, 29 parasites that were deficient in gametocytogenesis were successfully isolated (80).…”
Section: Piggybac-mediated Genetic Screeningmentioning
confidence: 99%